Identification of Violent Behavior in Serial Killers Using Handwriting - Fatima, Fatima (International Journal for Electronic Crime Investigation, 2021)
This review paper highlights the hidden violent and aggressive behavior in serial killers by analyzing its handwriting features. Identification of violent behavior in handwriting is very important as it has close relation with personality disorder or psychopathy and its associated crimes that can be overcome in future. Graphology is a scientific method to identify an individual’s personality, temperament, professional and intellectual behavior, social and inner capacities by evaluating and understanding patterns revealed in handwriting. Handwriting analysis describes a psycho-social-behavior like that of psychologist who emphasis on biological and psychic components interactions revealed in one’s handwriting e.g. serial killers. Graphology experts approach advanced technology and research studies to facilitate the process of handwritten images of general public data and observe the signs of violence in their graphical handwritten features. It can be used as coherent and resourceful profiling instrument to enrich the information and to assist the forensic psychologists, psychiatrists and investigators in their investigation.